Acidic and basic self-assembling peptide and peptide-graphene oxide hydrogels: characterisation and effect on encapsulated nucleus pulposus cells. (15th April 2022) - Ligorio, Cosimo; Vijayaraghavan, Aravind; Hoyland, Judith A.; Saiani, Alberto
Abstract: Extracellular pH can have a profound effect on cell metabolism, gene and protein expression. Nucleus pulposus (NP) cells, for example, under acidic conditions accelerate the production of degradative enzymes and pro-inflammatory cytokines, leading ultimately to intervertebral disc degeneration, a major cause of back pain. Self-assembling peptide hydrogels constitute a well-established class of biomaterials that could be exploited as pH-tunable platform to investigate cell behaviour under normal and non-physiological pH. In this paper we formulated acidic (pH = 4) and basic (pH = 9) hydrogels, from the same octapeptide FEFKFEFK (F8) (F = phenyalanine, E = glutamic acid, K = lysine), to test the effect of non-physiological pH on encapsulated NP cells. Similarly, graphene oxide-containing F8 hydrogels (GO-F8) were formulated as stiffer analogues. Acidic and basic hydrogels showed peculiar morphologies and rheological properties, with all systems able to buffer within 30 minutes of exposure to cell culture media. NP cells seeded in acidic F8 hydrogels showed a more catabolic phenotype compared to basic hydrogels, with increased gene expression of degradative enzymes (MMP-3, ADAMTS-4), neurotrophic factors (NGF and BDNF) and NF-κB p65 phosphorylation. Acidic GO-F8 hydrogels also induced a catabolic response, although milder than basic counterparts and with the highest gene expression of characteristic NP-matrix components, aggrecan and collagen II. In all systems, the cellular response had a peak within 3 days of encapsulation, thereafter decreasing over 7 days, suggesting a 'transitory' effect of hydrogel pH on encapsulated cells. This work gives an insight on the effect of pH (and pH buffering) on encapsulated NP cells and offers new designs of low and high pH peptide hydrogels for 3D cell culture studies. Statement of significance: We have recently shown the potential of graphene oxide - self-assembling peptide hybrid hydrogels for NP cell culture and regeneration. Alongside cell carrier, self-assembling peptide hydrogels actually provide a versatile pH-tunable platform for biological studies. In this work we decided to explore the effect of non-physiological pH (and pH buffering) on encapsulated NP cells. Our approach allows the formulation of both acidic and basic hydrogels, starting from the same peptide sequence. We showed that the initial pH of the scaffold does not affect significantly cell response to encapsulation, but the presence of GO results in lower inflammatory levels and higher NP matrix protein production. This platform could be exploited to study the effect of pH on different cell types whose behaviour can be pH-dependent. Graphical abstract: Image, graphical abstract